A promise of ankles [large type] - McCall Smith, Alexander, 1948- (McCall Smith, Alexander, 1948- 44 Scotland Street series, 2021)
From the hugely popular 44 Scotland Street series comes the latest adventures of Bertie and his family and friends. The winds of change are blowing through Scotland Street. Though Bertie is getting older, he can't resist an adventure to escape his domineering mother, and Bruce, ever the navel-gazer, will have to bring his best self to navigate the complexities of the pas de deux. While Alexander McCall Smith's delightfully warm and witty comedy takes some surprising turns, the improbable adventures of this quirky cast of Scots will affirm the heart and joy in Edinburgh's New Town.